Endothelial precursor cells stimulate pericyte‐like coverage of bone marrow‐derived mesenchymal stem cells through platelet‐derived growth factor‐BB induction, which is enhanced by substance P. (6th November 2017) - Zhang, Mingzi; Ahn, Woosung; Kim, Sumin; Hong, Hyun Sook; Quan, Chengshi; Son, Youngsook
Abstract: Objective: The aim of this study was to evaluate the angiogenicity of a combination of BM‐EPCs and BM‐MSCs in vitro in the presence of SP and its working mechanism. Methods: BM‐MSCs and BM‐EPCs were cocultured with or without SP. ELISA and RT‐PCR were performed to detect angiogenic factors such as VEGF and PDGF‐BB. N‐cadherin was detected by Western blot analysis. The tubular network‐forming ability was evaluated by a Matrigel tube‐forming assay. Results: BM‐EPCs coculture with BM‐MSCs strongly stimulated the recruitment of BM‐MSCs onto the BM‐EPC‐generated endothelial tubular network. Upon SP treatment, endothelial branching point, tubule length, and tubular recruitment of BM‐MSCs were further increased and stabilized. The coculture of BM‐EPCs and BM‐MSCs synergistically stimulated expression of VEGF, VEGF receptor, N‐cadherin, and PDGF‐BB, all of which were further enhanced by SP treatment. Blockade of PDGF‐BB by its functional blocking antibodies markedly reduced the BM‐MSC incorporation into the endothelial tubules. SP‐pretreated BM‐MSCs were preferentially incorporated into the preformed BM‐EPC tubular network. Conclusions: BM‐EPCs along with SP promote the pericyte‐like coverage of BM‐MSCs on endothelial tubules possibly through the induction of PDGF‐BB.